JURIDICAL REVIEW OF THE ROLE OF THE POLICE OF THE REPUBLIC OF INDONESIA IN LAW ENFORCEMENT OF MOTORCYCLE THEFT CASES (Case Study: Kesambi Police Cirebon City) - Muhamad Zaini Prakoso; Muhammad Karim Benzema; Wahyu Hidayat; Dimas Muhammad Fadilah (Jurnal Abdisci, 2025)
Abstract Background. The high crime rate in Indonesia is indeed difficult to prevent. Something that may still be rampant is motorcycle theft. Motorcycle theft in Indonesia is still rampant, especially in the Kesambi area. The rampant theft of motorcycles is very detrimental, especially to the individual himself. Aims. This study aims to analyze the form of motorcycle theft and evaluate its security to reduce the number of motorcycle thefts. Methods. The research method used is sociological juridical with a case study of the jurisdiction of the Kesambi Police Station, Cirebon City. Result. The research shows that the Kesambi Police have made several efforts to prevent motorcycle theft, but this must also be accompanied by community awareness. Conclusion. Some factors cause the crime of theft, including education-related factors related to the law, insufficient financial factors, family, environment, and a lack of firmness of law enforcement itself. Implementation. The author hopes that law enforcement will further increase its capacity and independence to overcome the crime of motorcycle theft. Various ways can be used, such as collaborating with other legal institutions, such as the prosecutor's office, or collaborating with local regional institutions to create conducive security and reduce the number of motorcycle theft crimes.